Penerapan Pembelajaran Bahasa Indonesia Berbasis Kompetitif Untuk Meningkatkan Keaktifan Dan Prestasi Belajar Siswa Kelas V - Wawan Mulyadi Purnama; Muh. Bisyrulhafi; Lia Wardatul Laili (Yayasan Azhar Amanaa Yogyakarta, 2026)
The low activity and learning achievement of students in learning Indonesian in the VB MI Jamaludin Paok Pondong class indicate the need to implement learning strategies that increase students' active involvement in the learning process. This study aims to describe the application of competition-based Indonesian language learning and to analyze its impact on students' learning activities and achievement. The research uses a qualitative, descriptive approach. Data were collected through observation, interviews, and documentation of teachers and students in VB classes, and then analyzed using the Miles and Huberman interactive model, which included data reduction, data presentation, and conclusion drawing, with validity testing through triangulation of sources and techniques. The results of the study show that competition-based learning is applied through various activities such as language quizzes, reading competitions, word-guessing games, presentations, simple debates, and group work, which create an active, interesting, and fun learning atmosphere. The application of this learning model increases student activity, as shown by the courage to ask and answer questions, express opinions, discuss, and work together, and has an impact on improving learning achievement because students become more motivated, focused, and more easily understand the material. These findings reinforce the effectiveness of competition-based learning in optimizing the processes and outcomes of learning Indonesian in elementary schools. The study's findings show that competition-based learning can be used as an alternative learning strategy for teachers to increase student activity and learning achievement through healthy, collaborative, and student-centered competition.